2013
DOI: 10.1002/anie.201308781
|View full text |Cite
|
Sign up to set email alerts
|

Non‐Pyrolytic, Large‐Scale Synthesis of Trichalcogenasumanene: A Two‐Step Approach

Abstract: Trichalcogenasumanenes were synthesized on a multigram scale through a two-step approach that takes advantage of non-pyrolytic cyclization and solventless ring contraction. Solid-state structure and photophysical investigations demonstrate that these compounds are promising candidates for electronic materials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
101
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 128 publications
(104 citation statements)
references
References 44 publications
2
101
0
1
Order By: Relevance
“…In the present study we report our attempts to insert heteroatoms like selenium and tellurium at the peripheral positions of the triphenylene rings using nucleophilic substitution reaction without any substitution on the triphenylene rings. During the course of the present study, Shao and co-workers 10 have reported the insertion of sulfur and selenium heteroatoms at the peripheral positions of the triphenylene rings (16)(17). In this case they succeeded in incorporating sulfur and selenium by electrophilic substitution reaction using n-BuLi as reagent followed by chalcogen (S, Se) insertion.…”
Section: Introductionmentioning
confidence: 82%
“…In the present study we report our attempts to insert heteroatoms like selenium and tellurium at the peripheral positions of the triphenylene rings using nucleophilic substitution reaction without any substitution on the triphenylene rings. During the course of the present study, Shao and co-workers 10 have reported the insertion of sulfur and selenium heteroatoms at the peripheral positions of the triphenylene rings (16)(17). In this case they succeeded in incorporating sulfur and selenium by electrophilic substitution reaction using n-BuLi as reagent followed by chalcogen (S, Se) insertion.…”
Section: Introductionmentioning
confidence: 82%
“…The higher the bowl inversion energy is, the more stable the chiral conformer will be. Several heterobuckybowls have been reported in the literature, some of them chiral ( Figure 9) [12,[58][59][60][61][62][63][64][65][66]. …”
Section: Heterobuckybowlsmentioning
confidence: 99%
“…More recently, Saito and co-workers prepared a triphosphasumanene trisulfide 13 derivative with a large dipole moment (12.0 D) [67]. The bowl depth of syn-isomer 13 is 0.46 Å, which is identical to triselenasumane 18 (0.47 Å) [64] and shallower than sumanene [24], whereas the anti-isomer of triphosphasumanene trisulfide 13 exists in an almost plane structure [67].…”
Section: Heterobuckybowlsmentioning
confidence: 99%
See 1 more Smart Citation
“…[11] Heterasumanenes can be created by replacing i) the benzyl carbon atoms with S, P, Si, Sn, and Ge; [12][13][14][15] and ii)the outer benzene rings with pyridine rings. [17] Compounds 1a-c are electron-rich owing to the presence of butoxy groups and chalcogen-containing rings,a nd 1a,b show ring strain because of the curved structure.T herefore, 1a-c have multiple chemically active sites:t he outer electron-rich C=C bonds,c halcogen atoms,a nd butoxy groups (shown as paths A, B, and Ci nS cheme 1). [17] Compounds 1a-c are electron-rich owing to the presence of butoxy groups and chalcogen-containing rings,a nd 1a,b show ring strain because of the curved structure.T herefore, 1a-c have multiple chemically active sites:t he outer electron-rich C=C bonds,c halcogen atoms,a nd butoxy groups (shown as paths A, B, and Ci nS cheme 1).…”
mentioning
confidence: 99%